Smart helmet to start the motorbike and to prevent accidents - Joy Mathavan, J.; Wijesekara, V.K.D.; Satheeskanth, N.; Wanasinghe, W.M.U.J.; Maathushan, M.; Wijenayake, V.V. (IOP Publishing, 2022)
Most of the motorbike riders meet a fatal end due to severe head injuries during accidents. Usually in Asian countries, riders are reluctant to wear helmets while riding motorbikes due to carelessness and negligence. This research aims at reducing the accidents that may occur due to such carelessness and at the same time, immediately report the accident to the emergency contact numbers. This research work is aimed at making the necessary conditions essential to start the motorbike. The rider needs to wear the helmet, should be free from consumption of alcohol and should take off the side stand before igniting the vehicle; failure of any one of this condition would not ignite the engine. The proposed system detects the accident occurrence as well. SMS will be sent to the emergency numbers through the GSM module. The prototype works on start mode, running mode and accident mode with different functionalities in each mode. The rider needs to clear the start on mode to ignite the engine and a smart system will continuously monitor the bike and rider in the running mode. In case of unexpected interruptions during running mode, the proposed system enters into accident mode and enables GSM to report the accident to the pre-registered phone number.